The Potential Use of Wood Vinegar as an Alternative Inhibitor to Enhance 5-Aminolevulinic Acid Production by Bacillus paramycoides - Farah; Fauzi, Ahmad; Monconegoro, Dicky Adihayyu; Nurani, Diana; Abraham, Silva (Bogor Agricultural University, Indonesia, 2025)
The expensive production of 5-aminolevulinic acid (ALA) as a plant growth stimulator led to an attempt to get an alternative substrate to reduce the production cost. Levulinic acid is the inhibitor of ALA dehydratase in ALA production. Wood vinegar, a liquid gas produced from wood combustion in airtight conditions, is known to contain 12-17 mM of levulinic acid. This study aims to explore the use of wood vinegar as a potential substitute for levulinic acid in the extracellular production of ALA by bacteria identified as Bacillus paramycoides through 16S rRNA sequence analysis. Adding precursor and inhibitor glutamate and 1% wood vinegar increased the ALA production to 174.3 µM, while the combination of glutamate and levulinic acid raised the ALA production to 179.9 µM. This study confirmed that wood vinegar can enhance the concentration of ALA and potentially substitute levulinic acid as an inhibitor in ALA production.